Legal Standing to the Corruption Eradication Commission as a Applicant for the Dissolution of a Political Party at the Constitutional Court: Legal Standing Komisi Pemberantasan Korupsi Sebagai Pemohon Pembubaran Partai Politik di Mahkamah Konstitusi - Saifulloh, Putra Perdana Ahmad; Kurnia Illahi, Beni; Ivana Barus, Sonia (Constitutional Court of the Republic of Indonesia, Indonesia, 2023)
This study criticizes the weakness of the regulation that solely grants Legal Standing for Petitioners seeking the Dissolution of Political Parties at the Constitutional Court to the Government, comprising the Attorney General and the Minister appointed by the President. Another approach is necessary for the Dissolution of Political Parties, which entails providing Legal Standing to the Corruption Eradication Commission, an Executive Entity that is not directly subordinate to the President. Public Trust in the Corruption Eradication Commission remains considerably high, rendering it suitable for representing the Government as a Petitioner for the Dissolution of a Political Party. Consequently, legislators must revise the Constitutional Court Law, the Corruption Eradication Commission Law, and the Constitutional Court's Regulation regarding Procedures for the Dissolution of Political Parties, thereby granting legal standing to the Corruption Eradication Commission as the Petitioner for Dissolving Political Parties.